Patients with Mild Cognitive Impairment Display Reduced Auditory Event-Related Delta Oscillatory Responses - Kurt, Pınar; Emek Savaş, Derya Durusu; Batum, Kübra; Turp, Bilge; Güntekin, Bahar; Karşıdağ, Sibel; Yener, Görsev (Hindawi Publishing Corporation, 410 Park Avenue, 15Th Floor, #287 Pmb, New York, Ny 10022 Usa, 2014)
Background. Event-related oscillations (ERO) may provide a useful tool for the identification of cognitive deficits in mild cognitive impairment (MCI) and Alzheimer's disease (AD). In the present study, we investigate peak-to-peak amplitude of auditory eventrelated delta oscillations of MCI subjects. Method. The study included twenty-two consecutive patients with MCI recruited in neurology clinic and 21 age-and education-matched normal elderly controls. A classical auditory oddball paradigm was used in the experiments. EEG was recorded from F-3, F-z, F-4, C-3, C-z, C-4, P-3, P-z, P-4, O-1, O-z, and O-2 locations. The maximum peak-to-peak amplitudes for each subject's averaged delta response (0.5-2.2Hz) weremeasured. Results. The amplitudes between groups differed significantly at the frontal and mid-centroparietal locations. ANOVA on delta responses revealed a significant effect for groups (F-(1.41) = 4.84, P = 0.033), indicating a larger delta response for healthy controls thanMCI subjects. Post hoc comparisons revealed that peak-to-peak delta response was significantly larger for healthy controls than for MCI over electrode sites F-3, F-z, F-4, C-z, C-4, and Pz. Discussion. Event-related delta frequency band seems to be the most affected oscillatory response in cognitive impairment due to AD. Therefore, it deserves to be investigated as a candidate electrophysiological biomarker in further studies.
Keywords: Alzheimers-Disease; Potentials; Theta; Dementia; Scale; Electroencephalography; Conversion; Diagnosis; Attention; Networks